DIRECTIVE SPEECH OF BALINESE WOMEN: A STUDY OF SOCIOLINGUISTICS - Denok Lestari (Journal of Language and Applied Linguistics, 2021)
This paper studies speech act phenomena in Denpasar area during Piodalan – temple ceremony which takes place every 210 days.  Balinese people, mostly women, work together hand in hand to get the offerrings and all equipments ready for the ceremony. During the preparation, Balinese people maintain the use of Basa Bali as their media of communication. From their conversation, it can be observed that the use of directive speech occurs more frequent than the use of other speech act functions, i.e. assertive, commissive, expressive, and declarative.  Directive speech is aimed to produce an effect in the form of the action of the hearer. It can be used in the form of imperative, interrogative, statement, or simply by giving hints. It is important to discuss the use of directive speech in order to gain the real message within the utterances which occur during the ritual.